Microvascular Dysfunction Following Cardioplegic Arrest and Cardiopulmonary Bypass: Impacts of Diabetes and Hypertension - Meghamsh Kanuparthy; Rishik Manthana; Himanshu Kaushik; Kathy Xiang; Jad Hamze; David Marimekala; Jun Feng; Frank W. Sellke (Biomedicines)
Cardioplegic arrest and cardiopulmonary bypass (CP/CPB) are known to engender microvascular dysfunction in patients undergoing cardiac surgery. These effects are significantly varied by patient comorbidities including diabetes and hypertension. Both diabetes and hypertension are associated with worse outcomes after cardiac surgery, partly related to increased microvascular complications. In this review, we examine several key facets of microvascular dysfunction after CP/CPB: microvascular endothelial and vasomotor dysfunction, altered gene and protein expression, endothelial adherens junction dysfunction, and programmed cell death as they relate to diabetes and hypertension. This review examines both classical techniques, including microvessel reactivity assays, and modern multiomic approaches to characterizing these microvascular changes.